Epidemiology of anophthalmia and microphthalmia: Prevalence and patterns in Texas, 1999–2009. Issue 9 (2nd August 2018) - Chambers, Tiffany M.; Agopian, A. J.; Lewis, Richard A.; Langlois, Peter H.; Danysh, Heather E.; Weber, Kari A.; Shaw, Gary M.; Mitchell, Laura E.; Lupo, Philip J.
Abstract : Anophthalmia and microphthalmia are a set of rare, yet severe, birth defects considered to be part of a spectrum of developmental ocular malformations ranging from smaller than average to completely absent eyes. Despite their clinical significance, little is known about the etiologies of these conditions. The goal of this study was to expand our understanding of the epidemiology of anophthalmia and microphthalmia. Data for this population‐based assessment were obtained from the Texas Birth Defects Registry (TBDR) and Center for Health Statistics for the period 1999–2009. Descriptive analyses and estimates of birth prevalence and prevalence ratios (PR) were determined for this defect. There were 1, 262 definite anophthalmia and microphthalmia patients identified in the TBDR, with an overall combined prevalence of 3.0 per 10, 000 live births. More than half (55.7%) of the patients had at least one chromosome abnormality or syndrome. In addition, 92.4% of nonsyndromic patients (i.e., have no recorded chromosome abnormalities or syndromes) had at least one additional birth defect. After adjustment for multiple factors, the prevalence of nonsyndromic anophthalmia and microphthalmia was higher among mothers who had ≥2 previous fetal deaths (PR = 1.43, 95% confidence interval [CI]: 1.03–1.97) and among mothers with any reported diabetes (PR = 2.08, 95% CI: 1.49–2.90). Our results confirm that children with anophthalmia and microphthalmia frequently have genetic syndromes or are born with other major birth defects. Our findings add to the limited body of literature on anophthalmia and microphthalmia as well as help define subgroups of women who are more likely to have children with this malformation.